IMPLEMENTASI KEBIJAKAN PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK MELALUI PROGRAM DESA RAMAH PEREMPUAN DAN PEDULI ANAK: (Studi di Desa Rembangkepuh, Kecamatan Ngadiluwih, Kabupaten Kediri) - Sutami, Beny (Jurnal Administrasi Publik, 2024)
Implementation of Women's Empowerment and Child Protection Policy through the Women-Friendly and Child-Caring Village Program (Study in Rembangkepuh Village, Ngadiluwih District, Kediri Regency). Women's empowerment and child protection policies aim to create an inclusive, just, and sustainable society. The implementation of this policy is realized through the Women Friendly Village and Child Care (DRPPA) program to overcome the challenges faced by women and children. This research uses a qualitative method with a descriptive approach. The results showed that several factors influenced the implementation of the DRPPA program. These factors include clear policy objectives, experienced human resources, adequate budget, but short implementation time. Effective communication is established between implementing organizations. In addition, the implementing agency has clear standard operating procedures, and SAPA volunteers show high commitment. Community support, economic conditions that need to be optimized, and political support from village elites also play an important role.